Risk factors of early psychoactive substances dependence among youth - R. M. Sadykov; N. L. Bolshakova (Вестник университета, 2022)
The article considers a number of factors that influence the use of psychoactive substances by young people in Russia: psychological, social, economic, medico-biological, spiritual and moral and others. The main reasons for psychoactive substance use among this age group are: neglect by parents, psychoactive substance use by parents and other relatives, abuse by parents and guardians, low family income, conflicts and lack of understanding of the age-specific characteristics of adolescents by parents, low motivation to study, low status among peer groups, youth informal groups. In addition to risk factors, protection factors – circumstances that reduce the likelihood of a person becoming involved with psychoactive substances have also been identified: a strong family, with a healthy and supportive psychological atmosphere, success in educational activities, parental involvement in the life of their children, etc.